A Proof for the Existence of Chaos in Diffusively Coupled Map Lattices with Open Boundary Conditions - Li-Guo Yuan; Qi-Gui Yang (Discrete Dynamics in Nature and Society)
We first study how to make use of the Marotto theory to prove rigorously the existence of the Li-Yorke chaos in diffusively coupled map lattices with open boundary conditions (i.e., a high-dimensional discrete dynamical system). Then, the recent 0-1 test for chaos is applied to confirm our theoretical claim. In addition, we control the chaotic motions to a fixed point with delay feedback method. Numerical results support the theoretical analysis.